Survey of ICT and Education in Africa : Rwanda Country Report - Farrell, Glen (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. ICT is central to Rwanda's Vision for 2020, and ICT in education is one of the core pillars of the country's national information and communications infrastructure policy and plan, adopted in 2000. Tremendous progress has been made since then and the country continues to receive plaudits and support from its development partners. The pace of development of a national ICT infrastructure is remarkable as is the progress within the education system on disseminating computers and providing connectivity and teacher training. Moreover, there is a nationwide effort to provide universal access to both infrastructure and the Internet in order to facilitate ICT4D in the broadest sense.